Advancing the application of bio-oils by co-processing with petroleum intermediates: A review. (June 2021) - Han, Xue; Wang, Haoxiang; Zeng, Yimin; Liu, Jing
Highlights: Co-processing bio-oils with petrocrudes in existing refineries is cost-effective. Up-to-date R&D activities on bio-oil co-refining are reviewed. Recent advancements of co-processing using fluid catalytic cracking are discussed. Significant knowledge gaps are addressed for further studies. Abstract: Crude bio-oils, as sustainable and renewable energy sources generated from thermochemical conversion of forest, agriculture, waste and algae biomass feedstocks, have attracted particular attention to partially and even completely replace the fossil fuels over the past decades. However, due to their undesirable qualities such as high oxygen content, thermal instability, and high corrosivity, further upgrading is required for the direct application of bio-oils for petrol engines or thermal power plants. Various upgrading pathways, including emulsification, hydrotreating, supercritical fluid treatment, and co-processing are being investigated by different international research groups to produce marketable drop-in renewable transportation biofuels. Among them, co-processing bio-oils with petroleum streams in existing refineries is recognized as a more promising solution compared to other conventional upgrading methods because of less capital investment and higher fuel productivity. This work reviewed the up-to-date research activities in bio-oil co-processing including process scale-up, focusing more on the most recent work about pyrolysis oils co-processing in the fluid catalytic cracking (FCC) unit and its industrial implementation. The significant knowledge gaps in the co-processing are also outlined for future investigations.